Crystalline polyester resin and adhesive composition using same
A crystalline polyester resin adhesive, formulated without metal sulfonate salts and optimized with specific monomer ratios, addresses the limitations of existing adhesives by providing superior adhesion, blocking resistance, and water resistance, making it suitable for food packaging.
Patent Information
- Application Number
- JP2022501896
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-17
- Filing Date
- 2021-02-16
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-02-16
AI Technical Summary
Existing polyester resin adhesives face challenges with incomplete peel strength, poor blocking resistance, and hygiene issues due to the use of metal sulfonate salts, particularly in crystalline polyester resin formulations.
A crystalline polyester resin is developed without metal sulfonate salts, composed of specific ratios of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, and 1,4-butanediol, with an acid value of 100 to 600 eq/t, a glass transition temperature of -30 to 30°C, and a melting point of 70 to 160°C, to achieve excellent adhesion, blocking resistance, and water resistance.
The crystalline polyester resin adhesive composition exhibits excellent storage stability, adhesion, blocking resistance, and water resistance, making it suitable for food packaging applications while ensuring hygiene and safety standards.
Smart Images

Figure 0007659745000001 
Figure 0007659745000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a crystalline polyester resin and an aqueous dispersion of a polyester resin, and more particularly to an adhesive which contains an aqueous dispersion of a polyester resin as a main component and which is particularly excellent in storage stability, adhesion, blocking resistance and water resistance. [Background technology]
[0002] Polyester resins are widely used as raw materials for resin compositions used in paints, coating agents, adhesives, etc. Polyester resins are generally composed of polycarboxylic acids and polyhydric alcohols. By selecting and combining the polycarboxylic acids and polyhydric alcohols, the molecular weight can be freely controlled, and the resulting polyester resins are used in a variety of applications, including paints and adhesives.
[0003] In the molecular design of polyester resins, the selection of copolymerization components is important. Polyvalent carboxylic acid components and polyhydric alcohol components can be broadly classified into aromatic, aliphatic, and alicyclic. The glass transition temperature, which indicates the flexibility of polyester resins, can be determined by the selection of these components. In terms of usage form, they are generally used by applying them to substrates as organic solvent-dissolved products or aqueous dispersions, but in recent years, aqueous dispersions have become particularly popular due to environmental concerns.
[0004] In recent years, polyester containers, which have excellent transparency and recyclability, have been widely used as packaging materials for fresh foods such as vegetables and fruits. Complete sealing can extend the expiration date of fresh foods, and they are attracting attention as a candidate for revolutionizing food distribution. Accordingly, the lid material of the packaging material is required to be hygienic, have reliable adhesion until the contents are removed, have blocking resistance when the film is wound, and be water-resistant to prevent clouding due to moisture in the contents.
[0005] For example, Patent Document 1 proposes an aqueous dispersion containing a polyester resin (A) having a glass transition temperature of 50° C. or higher and a polyester resin (B) having a glass transition temperature of 30° C. or lower. Patent Document 2 proposes a crystalline copolymerized polyester resin having 75 mol % or more of a linear aliphatic diol component having 4 to 10, a melting point of 90° C. or higher and 130° C. or lower, a polyvalent carboxylic acid component containing an aromatic dicarboxylic acid having a sulfonic acid metal salt in the range of 2 mol % or higher and 5 mol % or lower, and an acid value of less than 4 KOHmg / g. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5241232 [Patent Document 2] WO2015 / 045633 publication DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] However, in Patent Document 1, the polyester resin (B) is amorphous, and the peel strength described in the examples is not practical, and there is a problem in achieving both blocking resistance and heat sealability. In addition, in Patent Document 2, although the polyester resin is crystalline, it contains an aromatic dicarboxylic acid having a metal sulfonate, and there are problems with hygiene and water resistance.
[0008] As a result of extensive research aimed at solving the above problems, the present invention was completed based on the discovery that a crystalline polyester that does not use a metal sulfonate has high adhesion, blocking resistance, and water resistance.
[0009] That is, an object of the present invention is to provide an adhesive composition that is excellent in storage stability, high adhesion, blocking resistance and water resistance. [Means for solving the problem]
[0010] A crystalline polyester resin having copolymerization components of a polycarboxylic acid component and a polyhydric alcohol component, containing 30 to 70 mol % of terephthalic acid and 10 to 60 mol % of 1,4-cyclohexanedicarboxylic acid as the polycarboxylic acid component and 50 mol % or more of 1,4-butanediol as the polyhydric alcohol component, having an acid value of 100 to 600 eq / t, a glass transition temperature of -30 to 30°C, and a melting point of 70 to 160°C.
[0011] The content of the aromatic dicarboxylic acid component having a sulfonate group as the polyvalent carboxylic acid component of the crystalline polyester resin is preferably less than 1 mol %.
[0012] A polyester resin aqueous dispersion containing the crystalline polyester resin. An adhesive composition containing the polyester resin aqueous dispersion. A laminated film obtained by laminating the adhesive composition and a thermoplastic resin film. The thermoplastic resin film is preferably a polyester-based resin film, and the thickness of the adhesive composition layer is preferably in the range of 1 to 10 μm.
[0013] A packaging material comprising the laminated film as a constituent component. A lid material for a food packaging container comprising the packaging material as a constituent component. A food packaging container which is a laminate of the lid material and a polyester-based resin. Effect of the Invention
[0014] The crystalline polyester resin of the present invention can be used to prepare an aqueous dispersion having excellent storage stability, adhesion, blocking resistance, and water resistance, even without using a metal sulfonate. In particular, an adhesive composition using the crystalline polyester resin aqueous dispersion has excellent adhesion to a substrate when heat-sealed as a lid material for a packaging container. Furthermore, since it uses FDA-approved raw materials, it is safe and can be suitably used as a packaging material for fresh foods, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail.
[0016] <Crystalline polyester resin> The crystalline polyester resin of the present invention has a chemical structure that can be obtained by polycondensation of a polycarboxylic acid and a polyhydric alcohol, and the polycarboxylic acid and the polyhydric alcohol each consist of one or more selected components.
[0017] The polyvalent carboxylic acid constituting the crystalline polyester resin of the present invention is preferably an aromatic dicarboxylic acid, an alicyclic dicarboxylic acid and / or an aliphatic dicarboxylic acid.
[0018] When the total amount of polyvalent carboxylic acid components is taken as 100 mol%, the copolymerization amount of terephthalic acid must be 30 to 70 mol%, preferably 35 to 65 mol%, and more preferably 40 to 60 mol%. By making the copolymerization amount 30 mol% or more, the obtained polyester resin becomes crystalline and has good blocking resistance. Also, by making it 70 mol% or less, the melting point does not become too high, and it can be melted by the heat amount during heat sealing, and the adhesiveness is good.
[0019] When the total amount of polyvalent carboxylic acid components is taken as 100 mol%, the copolymerization amount of 1,4-cyclohexanedicarboxylic acid must be 10 to 60 mol%, preferably 15 to 55 mol%, and more preferably 20 to 50 mol%. By making the copolymerization amount 10 mol% or more, the glass transition temperature of the obtained polyester resin does not become too high, and the adhesiveness becomes good. Also, by making it 60 mol% or less, the crystallinity of the polyester resin increases, and the blocking resistance becomes good.
[0020] When the total amount of polyvalent carboxylic acid components is taken as 100 mol%, the total copolymerization amount of terephthalic acid and 1,4-cyclohexanedicarboxylic acid is preferably 40 mol% or more, more preferably 50 mol% or more, even more preferably 60 mol% or more, even more preferably 70 mol% or more, and particularly preferably 80 mol% or more. Also, it is preferably 99 mol% or less, more preferably 95 mol% or less, and even more preferably 90 mol% or less. By keeping it within the above range, adhesion and blocking resistance are improved.
[0021] When the total amount of polyvalent carboxylic acid components is 100 mol%, the copolymerization amount of aliphatic dicarboxylic acid is preferably 40 mol% or less, more preferably 35 mol% or less, and even more preferably 30 mol% or less. By making it 40 mol% or less, the hydrolysis resistance of the crystalline polyester resin is improved and the water resistance is good. When aliphatic dicarboxylic acid is copolymerized, it is preferably 5 mol% or more, more preferably 10 mol% or more.
[0022] As the polycarboxylic acid component other than terephthalic acid and 1,4-cyclohexanedicarboxylic acid, it is preferable to use isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-naphthalenedicarboxylate, trimellitic acid, adipic acid, sebacic acid, fumaric acid, maleic acid or dimer acid, which may be used alone or in combination of two or more. These compounds are raw materials described and approved in FDA (Food and Drug Administration) standard 175.300 (b) (3) (vii) (revised version on April 1, 2014), and can be suitably used for food packaging materials. Among these, it is preferable to combine isophthalic acid, adipic acid or sebacic acid in terms of adhesion to the substrate, water resistance, price, etc. The copolymerization amount of these polycarboxylic acid components is preferably 40 mol% or less, more preferably 35 mol% or less, and even more preferably 30 mol% or less, when the total amount of the polycarboxylic acid components is 100 mol%. By setting the content to 40 mol % or less, the hydrolysis resistance of the crystalline polyester resin is improved and the water resistance is good. On the other hand, although there is no particular restriction on the lower limit, when these polyvalent carboxylic acids are copolymerized, the lower limit is preferably 5 mol % or more, and more preferably 10 mol % or more.
[0023] When the total amount of the polyhydric alcohol components is 100 mol%, the copolymerization amount of 1,4-butanediol must be 50 mol% or more, preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, still more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%. By making it 50 mol% or more, the obtained polyester resin becomes crystalline and has good blocking resistance.
[0024] As the polyhydric alcohol component other than 1,4-butanediol, it is preferable to use a compound described in FDA Standard 175.300(b)(3)(vii) (revised version on April 1, 2014). Specific examples include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 2,2-dimethyl-1,3-propanediol, glycerol, mannitol, pentaerythritol, trimethylolethane, and trimethylolpropane. The copolymerization amount of these polyhydric alcohol components must be 50 mol% or less, preferably 40 mol% or less, more preferably 30 mol% or less, even more preferably 20 mol% or less, even more preferably 10 mol% or less, particularly preferably 5 mol% or less, and may be 0 mol%. By making it 50 mol% or less, the obtained polyester resin becomes crystalline and has good blocking resistance.
[0025] In the crystalline polyester resin of the present invention, it is also preferable to introduce a branched structure by copolymerizing a small amount of a trifunctional or higher polyvalent carboxylic acid component or a polyhydric alcohol component. This makes it possible to form a tougher layer of the adhesive composition (hereinafter also referred to as an adhesive layer), and the effect of improving water resistance can be exhibited. Specific examples include trimellitic anhydride, ethylene glycol bisanhydrotrimellitate, trimethylolpropane, glycerin, and pentaerythritol. The copolymerization amount of these trifunctional or higher polyvalent carboxylic acid components and polyhydric alcohol components is preferably 0.5 mol% or more, more preferably 1 mol% or more, when the total amount of all polyvalent carboxylic acid components and all polyhydric alcohol components is 200 mol%. In addition, it is preferably 5 mol% or less, more preferably 4 mol% or less, and even more preferably 3 mol% or less.
[0026] When the total amount of the polyvalent carboxylic acid components is taken as 100 mol%, the content of the aromatic dicarboxylic acid component having a sulfonate group is preferably less than 1 mol%. More preferably, it is 0.5 mol% or less, even more preferably, it is 0.1 mol% or less, and particularly preferably, it is 0 mol%. Since the aromatic dicarboxylic acid component having a sulfonate group is an acid component not approved by the FDA, the crystalline polyester resin of the present invention can be used for food contact applications by reducing the amount of the aromatic dicarboxylic acid component having a sulfonate group. Examples of the aromatic dicarboxylic acid component having a sulfonate group include 5-sulfoisophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5[4-sulfophenoxy]isophthalic acid, and alkali metal salts thereof. Examples of the alkali metal salt include lithium, sodium, potassium, and the like. Specific examples include sodium 5-sulfonatoisophthalate, potassium 5-sulfonatoisophthalate, sodium 4-sulfonaphthalene-2,7-dicarboxylate, sodium 5[4-sulfophenoxy]isophthalate, and the like.
[0027] When the total amount of the polyhydric alcohol components is taken as 100 mol%, the content of the polyhydric alcohol component having a sulfonate group is preferably less than 1 mol%. More preferably, it is 0.5 mol% or less, even more preferably, it is 0.1 mol% or less, and particularly preferably, it is 0 mol%. Since the polyhydric alcohol component having a sulfonate group is an alcohol component not approved by the FDA, the crystalline polyester resin of the present invention can be used for food contact applications by reducing the amount of the polyhydric alcohol component having a sulfonate group. Examples of the polyhydric alcohol component having a sulfonate group include the sodium salt of 2-sulfo-1,4-butanediol and the sodium salt of 2,5-dimethyl-3-sulfo-2,5-hexanediol.
[0028] In addition, in order to impart an acid value, an acid anhydride such as trimellitic anhydride or pyromellitic anhydride may be added after polymerization of the polyester resin. When added after, the total amount of the polyvalent carboxylic acid component and the polyhydric alcohol component may exceed 200 mol%. In this case, the total amount of the composition excluding the component to which the acid anhydride is added after is calculated as 200 mol%.
[0029] When producing the crystalline polyester resin of the present invention, the polymerization catalyst that can be used includes, for example, titanium compounds such as tetra-n-butyl titanate, tetraisopropyl titanate, and titanium oxyacetylcetonate, antimony compounds such as antimony trioxide and tributoxyantimony, germanium compounds such as germanium oxide and tetra-n-butoxygermanium, and acetates of magnesium, iron, zinc, manganese, cobalt, and aluminum. These catalysts can be used alone or in combination of two or more.
[0030] The method of the polymerization condensation reaction for producing the crystalline polyester resin of the present invention is not particularly limited, and examples thereof include 1) a method of heating a polycarboxylic acid and a polyhydric alcohol in the presence of an arbitrary catalyst, passing through a dehydration esterification step, and then carrying out a polyhydric alcohol removal / polycondensation reaction, and 2) a method of heating an alcohol ester of a polycarboxylic acid and a polyhydric alcohol in the presence of an arbitrary catalyst, passing through an ester exchange reaction, and then carrying out a polyhydric alcohol removal / polycondensation reaction, etc. In the above methods 1) and 2), a part or all of the acid component may be replaced with an acid anhydride.
[0031] The glass transition temperature (Tg) of the crystalline polyester resin of the present invention is −30 to 30° C., preferably −25 to 25° C., and more preferably −20 to 20° C. By making it equal to or higher than the lower limit, it is possible to suppress the occurrence of blocking when the laminated film is wound into a roll. By making it equal to or lower than the upper limit, the resin has flexibility even when peeled off at room temperature, and the adhesiveness is good.
[0032] The term "crystalline" as used herein refers to a material that exhibits a clear melting peak during heating from -100°C to 250°C at a rate of 20°C / min using a differential scanning calorimeter (DSC).
[0033] The melting point (Tm) of the crystalline polyester resin of the present invention is 70 to 160°C, preferably 75 to 155°C, and more preferably 80 to 150°C. By setting the melting point to the lower limit or higher, the crystallinity becomes good and excellent blocking resistance can be exhibited. Furthermore, by setting the melting point to the upper limit or lower, the resin melts sufficiently even at low temperatures, and no sealing defects occur even when heat sealing is performed at low temperatures. Furthermore, even if a plastic film such as a polyester film is used as the substrate to be coated, problems such as deformation of the substrate do not occur.
[0034] The reduced viscosity (ηsp / c) of the crystalline polyester resin is preferably 0.2 to 1.2 dl / g. More preferably, it is 0.4 to 1.1 dl / g, and even more preferably, it is 0.6 to 1.0 dl / g. By making it equal to or greater than the lower limit, the resin coagulation force is improved, and excellent adhesiveness can be exhibited. Also, by making it equal to or less than the upper limit, an aqueous dispersion can be prepared. The reduced viscosity can be arbitrarily adjusted by changing the polymerization time, temperature, and degree of reduced pressure during polymerization (in the case of reduced pressure polymerization) of the crystalline polyester resin. The reduced viscosity is a value measured using an Ubbelohde viscometer at a sample concentration of 0.125 g / 25 ml, a measurement solvent of chloroform, and a measurement temperature of 25°C.
[0035] The acid value of the crystalline polyester resin is 100 to 600 eq / t, preferably 150 to 550 eq / t, and more preferably 200 to 500 eq / t. By making it equal to or less than the upper limit, the molecular weight is not low, so that the resin cohesive force is good and excellent adhesiveness can be exhibited. In addition, by making it equal to or more than the lower limit, an aqueous dispersion can be prepared.
[0036] The number average molecular weight (Mn) of the crystalline polyester resin is preferably 4000 to 40000. More preferably, it is 6000 to 35000, and further preferably, it is 8000 to 30000. By making it equal to or more than the lower limit, the resin coagulation force becomes good, and excellent adhesiveness can be exhibited. Also, by making it equal to or less than the upper limit, an aqueous dispersion can be prepared. The number average molecular weight can be arbitrarily adjusted by changing the polymerization time, temperature, and degree of reduced pressure during polymerization (in the case of reduced pressure polymerization) of the crystalline polyester resin. The number average molecular weight is a value measured by gel permeation chromatography (hereinafter, GPC, standard substance: polystyrene resin, mobile phase: tetrahydrofuran or chloroform).
[0037] <Polyester resin water dispersion> The polyester resin aqueous dispersion of the present invention is an aqueous dispersion containing the above-mentioned crystalline polyester resin and water, and optionally containing an organic solvent.
[0038] The boiling point of the organic solvent used in the polyester resin water dispersion of the present invention is preferably 100° C. or higher, more preferably 105° C. or higher, even more preferably 110° C. or higher, particularly preferably 115° C. or higher, and most preferably 120° C. or higher. When the boiling point is 100° C. or higher, the crystalline polyester resin can be melted and easily dispersed in water. Also, the boiling point is preferably 180° C. or less, more preferably 175° C. or less, even more preferably 170° C. or less, particularly preferably 165° C. or less, and most preferably 160° C. or less. When the boiling point is 180° C. or less, there is almost no residual solvent during drying, and problems such as blocking during winding do not occur.
[0039] The organic solvent used in the polyester resin water dispersion of the present invention is not particularly limited, but includes alcohols such as isopropyl alcohol, isobutyl alcohol, and isoamino alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether (hereinafter also referred to as "n-butyl cellosolve" or "n-BuCS"), ethylene glycol mono-tert-butyl ether (hereinafter also referred to as "t-butyl cellosolve" or "t-BuCS"), propylene glycol monobutyl ether, and methyl ethyl ketone. These organic solvents can be used alone or in combination of two or more kinds. Among them, n-butyl cellosolve and t-butyl cellosolve are particularly preferred.
[0040] The organic solvent is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 100 parts by mass or less, and particularly preferably 50 parts by mass or less, relative to 100 parts by mass of the crystalline polyester resin. By making it less than the upper limit, the residual solvent during drying is reduced, and problems such as blocking during winding are prevented. In addition, the storage stability is also good. The lower limit is not particularly limited, but industrially, there is no problem if it is 1 part by mass or more, and it is also acceptable to use 10 parts by mass or more.
[0041] The amount of water is preferably 150 parts by mass or more, more preferably 170 parts by mass or more, and even more preferably 200 parts by mass or more, relative to 100 parts by mass of the crystalline polyester resin. By making it equal to or more than the lower limit, the crystalline polyester resin is dispersed in water, and the polyester resin aqueous dispersion of the present invention can be obtained. In addition, it is preferably 500 parts by mass or less, more preferably 450 parts by mass or less, and even more preferably 400 parts by mass or less. By making it equal to or less than the upper limit, production efficiency is improved, which is industrially advantageous.
[0042] The particle size of the crystalline polyester resin phase contained in the polyester resin aqueous dispersion of the present invention is preferably 30 nm or more, more preferably 40 nm or more, even more preferably 50 nm or more, and particularly preferably 60 nm or more. By making it equal to or greater than the lower limit, the film-forming property is improved, fusion and aggregation between dispersed particles are suppressed, and thickening and poor dispersion do not occur. In addition, it is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 150 nm or less. By making it equal to or less than the upper limit, excellent dispersion stability and film-forming property can be maintained, and the appearance and performance of the obtained film are good. Here, the particle size refers to the particle size of the crystalline polyester resin, and when two or more types of polyester resins are contained, such as when another polyester resin is further contained, it refers to the average particle size of the two or more types of polyester resins.
[0043] The polyester resin aqueous dispersion of the present invention can be suitably used as a raw material for adhesives, coating agents and heat sealing agents, and is particularly suitable for adhesive applications.
[0044] <Adhesive composition> The adhesive composition of the present invention is a composition containing the above-mentioned polyester resin aqueous dispersion as an essential component.
[0045] The adhesive composition of the present invention may be blended with other polyester resins or aqueous dispersions thereof, and various additives, as long as the performance of the present invention is not impaired. The additives are not particularly limited, but it is preferable to use an antiblocking agent or the like.
[0046] Examples of the antiblocking agent include inorganic particles, organic particles, and waxes, and can be contained to the extent that the adhesiveness and antiblocking properties are not deteriorated. These antiblocking agents can be used alone or in combination of two or more. When the antiblocking agent is contained, it is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the crystalline polyester resin. By containing the antiblocking agent in an amount equal to or more than the lower limit, the antiblocking effect can be expressed. In addition, it is preferably 5 parts by mass or less, more preferably 3 parts by mass or less. By keeping it equal to or less than the upper limit, the adhesiveness and transparency can be maintained.
[0047] Examples of inorganic particles include inorganic particles containing oxides, hydroxides, sulfates, carbonates, or silicates of metals such as magnesium, calcium, barium, zinc, zirconium, molybdenum, silicon, antimony, or titanium. Among these inorganic particles, silica gel particles are particularly preferred. The shape of the particles is not limited and may be any shape such as powder, granules, granules, platelets, or needles.
[0048] Examples of organic particles include polymer particles such as polymethyl methacrylate resin, polystyrene resin, nylon resin, melamine resin, benzoguanamine resin, phenol resin, urea resin, silicone resin, methacrylate resin, or acrylate resin, or cellulose powder, nitrocellulose powder, wood powder, waste paper powder, rice husk powder, starch, etc. The polymer particles can be obtained by polymerization methods such as emulsion polymerization, suspension polymerization, dispersion polymerization, soap-free polymerization, and microsuspension polymerization. The organic particles can be used within a range that does not impair the effects of the present invention. The shape of the particles is not limited and may be any shape such as powder, granule, granular, plate-like, or needle-like.
[0049] Specific examples of waxes include liquid paraffin, natural paraffin, microwax, synthetic paraffin, hydrocarbon waxes such as polyethylene wax, fatty acid waxes such as stearic acid, fatty acid amide waxes such as stearic acid amide, palmitic acid amide, methylene bis stearamide, ethylene bis stearamide, oleic acid amide, and esylic acid amide, ester waxes such as lower alcohol esters of fatty acids, polyhydric alcohol esters of fatty acids, and fatty acid polyglycol esters, alcohol waxes such as cetyl alcohol and stearyl alcohol, olefin waxes, natural waxes such as castor wax and carnauba wax, and metal soaps derived from fatty acids having 12 to 30 carbon atoms. The waxes can be used within a range that does not impair the effects of the present invention.
[0050] <Laminated film> The laminated film of the present invention is a film in which an adhesive layer made of the adhesive composition of the present invention is laminated on at least one side of a base film. The laminated film is obtained by applying the adhesive composition to the base film and then carrying out a drying treatment.
[0051] The substrate film is not particularly limited as long as it can form an adhesive layer from the adhesive composition of the present invention, but is preferably a thermoplastic resin film, such as a polyester-based resin film, a polypropylene-based resin film, a polyamide-based resin film, a polyvinyl alcohol-based resin film, or a polyvinylidene chloride-based resin film. Of these, a polyester-based resin film is more preferred because it is suitable as a lid material for food packaging containers.
[0052] The thickness of the base film is preferably 5 μm or more, more preferably 10 μm or more. By making the thickness equal to or more than the lower limit, the durability of the base film is improved. Also, the thickness is preferably 50 μm or less, more preferably 30 μm or less. By making the thickness equal to or less than the upper limit, the base film can be practically used as a lid material for food packaging containers.
[0053] The thickness of the adhesive layer is preferably 1 μm or more, more preferably 2 μm or more. By making the thickness equal to or more than the lower limit, the adhesiveness is improved. Also, the thickness is preferably 10 μm or less, more preferably 5 μm or less. By making the thickness equal to or less than the upper limit, the adhesiveness and heat sealability are improved.
[0054] The laminated film of the present invention has excellent adhesiveness and is therefore suitable as a component of packaging materials. In particular, it is suitable as a lid material for food packaging containers for fresh foods and the like. When used as a lid material for food packaging containers, the adhesive layer surface of the laminated film can be laminated to the food packaging container to seal the contents. The food packaging container is not particularly limited, but is preferably made of a polyester resin. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the examples. In the examples and comparative examples, parts simply indicate parts by mass.
[0056] (Physical property evaluation method)
[0057] Determination of composition of copolymer polyester resin 400MHz 1 H-nuclear magnetic resonance spectrometer ( 1 The molar ratios of the polycarboxylic acid and polyhydric alcohol components constituting the copolymerized polyester were determined using H-NMR. Deuterated chloroform was used as the solvent.
[0058] Crystalline melting point (Tm) and glass transition temperature (Tg) Using a differential scanning calorimeter (DSC) DSC-220 manufactured by Seiko Instruments Inc., 5 mg of a sample (crystalline polyester resin) was sealed in an aluminum press-lid type container, and the temperature was measured from -100°C to 250°C at a temperature increase rate of 20°C / min, and the maximum peak temperature of the heat of fusion was determined as the crystalline melting point. The glass transition temperature was also determined using the above-mentioned measuring device under the same conditions as above, as the temperature at the intersection of an extension of the baseline below the glass transition temperature and a tangent showing the maximum slope between the rising part of the peak and the apex of the peak.
[0059] Storage stability The polyester resin aqueous dispersion was stored (left stationary) at 25°C for 6 months, and the changes in appearance and shape (viscosity) were observed. <Evaluation criteria> ○: No change in appearance or shape (viscosity). △: Became cloudy but the shape (viscosity) did not change. ×: Viscosity increased, separation occurred, or poor dispersion occurred.
[0060] Preparation of laminated film for evaluation The adhesive compositions obtained in the Examples and Comparative Examples were applied to the corona-treated surface of a 25 μm-thick polyester film (E5107, manufactured by Toyobo Co., Ltd.) to a thickness of 3 g / m 2 The coating was then dried at 160° C. for 30 seconds to obtain a laminated film for evaluation.
[0061] (1) Peel strength (adhesion) The adhesive layer surface of the laminated film for evaluation was attached to a 350 μm thick unstretched amorphous PET sheet at a temperature of 160°C and a pressure of 2.8 kgf / cm. 2 Then, a test piece having a width of 25 mm was cut out and subjected to a 180° peel test at a tensile speed of 100 mm / min at 25° C. to measure the peel strength. <Evaluation criteria> ○:800gf / 25mm or more △: 500gf / 25mm or more and less than 800gf / 25mm ×: Less than 500gf / 25mm
[0062] (2) Blocking resistance The adhesive layer surface of the laminated film for evaluation was laminated on the corona untreated surface of a polyester film (E5107, manufactured by Toyobo Co., Ltd.) to prepare a test sample. 2 The specimens were stored under a pressure of 1000 psi for one day, and the blocking resistance was evaluated according to the following criteria. <Evaluation criteria> ○: The test sample had absolutely no tack. Δ: The test sample had a slight amount of tack, but it was not problematic in use. ×: The test sample had tack, to the extent that would cause problems in use.
[0063] (3) Water resistance The test pieces prepared for the evaluation of peel strength were immersed in water at 25° C. for one day. After that, the test pieces were measured according to the method for measuring peel strength, and the results were used to evaluate water resistance. <Evaluation criteria> ○:800gf / 25mm or more △: 500gf / 25mm or more and less than 800gf / 25mm ×: Less than 500gf / 25mm
[0064] Examples of crystalline polyester resins Synthesis of crystalline polyester resin (A-1) In a reaction vessel equipped with a stirrer, a thermometer, a heater, a cooling device, and a distillation cooler, 375 parts by mass of terephthalic acid, 225 parts by mass of 1,4-cyclohexanedicarboxylic acid, 132 parts by mass of adipic acid, 9 parts by mass of trimellitic anhydride, 813 parts by mass of 1,4-butanediol, and 0.5 parts by mass of tetrabutyl titanate were charged, and the temperature was raised to 220 ° C. while carrying out an esterification reaction for 4 hours. After the esterification reaction was completed, the pressure in the system was raised to 250 ° C. while reducing the pressure to 10 torr over 60 minutes, and further reduced to a vacuum of 1 torr or less, and a polycondensation reaction was carried out at 250 ° C. to a predetermined viscosity. Thereafter, nitrogen was flowed into the system, cooled to 220 ° C., and 27 parts by mass of trimellitic anhydride was added, and the reaction was carried out for 30 minutes. After the reaction was completed, the crystalline polyester resin was taken out and cooled to obtain a crystalline polyester resin (A-1).
[0065] Synthesis of crystalline polyester resins (A-2) to (A-15) Polyester resins (A-2) to (A-15) were synthesized in the same manner as in the synthesis example of crystalline polyester resin (A-1). The resin compositions and the measurement results of the physical properties are shown in Table 1.
[0066] [Table 1]
[0067] Example 1 Production Example of Polyester Resin Aqueous Dispersion (B) Manufacture of polyester resin moisture dispersion (B-1) The crystalline polyester resin (A-1) was dispersed in water according to the following procedure. 100 parts of the crystalline polyester resin (A-1), 40 parts of ethylene glycol monobutyl ether, 120 parts of methyl ethyl ketone, and 30 parts of isopropyl alcohol were charged into a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and the resin was dissolved at 80°C for 3 hours. Then, 3.6 parts of dimethylaminoethanol were added and stirred for 30 minutes. Then, 260 parts of hot water were added and stirred for 1 hour. Then, while raising the internal temperature to 100°C, methyl ethyl ketone and isopropyl alcohol were distilled off to obtain a polyester resin aqueous dispersion (B-1). The results of various property evaluations are shown in Table 2.
[0068] Examples 2 and 3, Reference Example 4, Examples 5 and 6, Reference Example 7, Examples 8 and 9, Comparative Examples 1 to 6 Polyester resin moisture dispersions (B-2) to (B-15) were obtained in the same manner as in the production example of Example 1. The results of evaluation of various properties are shown in Table 2.
[0069] JPEG0007659745000002.jpg190166
[0070] As is clear from Table 2, Examples 1 to 3, Reference Example 4, Examples 5 and 6, Reference Example 7, Example 8,In Comparative Example 9, the storage stability, adhesion, blocking resistance, and water resistance are well balanced and good. In contrast, in Comparative Example 1, the melting point of the polyester resin is high, and the storage stability of the aqueous dispersion is poor. Furthermore, the peel strength is low and the water resistance is poor. In Comparative Examples 2 and 3, the crystallinity of the polyester resin is low and it does not have a melting point, so the blocking resistance and water resistance are poor. In Comparative Example 4, the hydrolysis of the polyester resin is likely to proceed, and the storage stability and water resistance of the aqueous dispersion are poor. In Comparative Example 5, the acid value of the polyester resin is low, and the aqueous dispersion could not be obtained due to poor dispersion. Therefore, it was not possible to measure properties such as peel strength. In Comparative Example 6, 5-sulfoisophthalic acid was used, so the aqueous dispersion could be prepared, but the water resistance was poor. [Industrial Applicability]
[0071] The adhesive composition according to the present invention and the laminated film using the same have excellent adhesion to a substrate and blocking resistance when heat sealed as a lid for a packaging container.
Claims
1. A crystalline polyester resin having copolymerization components of a polyvalent carboxylic acid component and a polyhydric alcohol component, containing 30 to 70 mol % of terephthalic acid and 10 to 60 mol % of 1,4-cyclohexanedicarboxylic acid as the polyvalent carboxylic acid component and 100 mol % of 1,4-butanediol as the polyhydric alcohol component, having an acid value of 100 to 600 eq / t, a glass transition temperature of -30 to 30°C, and a melting point of 70 to 160°C.
2. 2. The crystalline polyester resin according to claim 1, wherein the content of the aromatic dicarboxylic acid component having a sulfonate group as the polyvalent carboxylic acid component is less than 1 mol %.
3. A polyester resin water dispersion comprising the crystalline polyester resin according to claim 1 or 2.
4. An adhesive composition comprising the polyester resin aqueous dispersion according to claim 3.
5. A laminated film comprising the adhesive composition according to claim 4 and a thermoplastic resin film laminated thereon.
6. 6. A laminated film, wherein the thermoplastic resin film according to claim 5 is a polyester-based resin film.
7. 7. The laminated film according to claim 5, wherein the thickness of the adhesive composition layer is in the range of 1 to 10 μm.
8. A packaging material comprising the laminate film according to any one of claims 5 to 7 as a constituent component.
9. A lid material for food packaging containers, comprising the packaging material according to claim 8 as a constituent component.
10. A food packaging container comprising a laminate of the covering material according to claim 9 and a polyester resin.
Citation Information
Patent Citations
Weed killer
JP1977041232A
The polyester sheet material and molding and manufacturing method thereof
JP1992503688A
Adhesive resin composition
JP1994108027A
Easy opening packaging material
JP2001328221A
Polyester resin aqueous dispersion and adhesive composition using the same
JP2014208741A